Pengaruh Teknik Stencil Print terhadap Keterampilan Seni Rupa Anak Kelompok B di RA Darul Ikhlas Kecamatan Lubuk Pakam - Mutiara Fadillah; Yusra Yusra; Mutia Sari; Anisaturrahmi Anisaturrahmi (Jurnal Raudhah, 2026)
The problems in this study were the low level of fine art skills among group B children at RA Darul Ikhlas and the fact that the stencil print technique had not yet been implemented in learning. This study aimed to determine the effect of the stencil print technique on the fine art skills of young children. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The research subjects consisted of 15 children from group B3 at RA Darul Ikhlas. The instrument used was an observation sheet with indicators including creating artwork based on creativity, mixing colors, and appreciating the finished artwork. Data analysis techniques used the Shapiro-Wilk normality test and the paired sample t-test. The findings showed: (1) the average pretest score (20.00) increased to 50.27 in the posttest;and (2) the results of the paired sample t-test obtained a calculated t-value of -34.152 with a significance of 0.000 (p < 0.05), which means that the stencil print technique has a significant effect on improving children's fine art skills. It is recommended that early childhood education teachers apply the stencil print technique as a learning innovation to develop young children's fine art skills.